Relationship between Knowledge and Using Personal Protective Equipment in Tuberculosis Ward and Polyclinic of Hospital X - Ekorini Listiowati; Fitria Eka Rianti (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Tuberculosis (TB) prevalence in Indonesia occupies the 2nd position globally; therefore, it is necessary to prevent TB transmission, including the use of Personal Protective Equipment (PPE) in high-risk individuals. This study aims to determine the relationship between nurses' knowledge and behavior in using PPE to prevent TB transmission in hospitals. This study used a cross-sectional design, with the research subjects of all nurses in the isolation room and the TB polyclinic in a private hospital (X) in Yogyakarta. The study was attended by 38 nurses, with a total sampling technique. Data were obtained using a questionnaire. The data analysis employed descriptive statistical tests and chi-square. This study’s results indicated that most nurses had good knowledge (31 people; 81.6%) and good behavior (32 people; 84.2%). Chi-square analysis revealed a significant relationship between knowledge and nurses' behavior in using PPE (p = 0.000). It was concluded that there was a significant relationship between knowledge and nurses' behavior in using PPE in the TB ward and polyclinic at Hospital X.